Pengaruh Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Manufaktue Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode 2020-2024 - Sahruni Sahruni; Burhanuddin Burhanuddin; Andi Mustika Amin; Anwar Ramli; Anwar Anwar (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine the effect of dividend policy on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative method with an associative approach to analyze the relationship between independent and dependent variables. The population consists of all food and beverage manufacturing companies listed on the IDX, while the sample is determined using a purposive sampling technique based on specific criteria. The data used in this study are secondary data obtained from the companies’ annual financial statements published on the official IDX website. Data analysis is conducted using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that dividend policy has a positive and significant effect on firm value. This finding suggests that companies implementing higher and more consistent dividend policies tend to have higher firm value as perceived by investors. The results support signaling theory, which explains that dividend policy serves as a positive signal regarding a company’s future prospects and financial performance. Therefore, dividend policy can be considered an important strategic decision for management in enhancing firm value and attracting investor confidence.